Cambodia : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper for Cambodia explores the implications for long-term sustainable growth from cross-country analysis of the sources of growth. Cambodia's low labor productivity, inadequate and expensive infrastructure, and a cumbersome regulatory environment do not bode well for future sustainable growth. Favorable external conditions, including foreign aid flows and trade agreements, have helped propel growth. As with other transition economies, Cambodia lags in institutional and market development. Cambodia has also benefited from large aid inflows, which have boosted economic activity.